2021
DOI: 10.1007/jhep08(2021)138
|View full text |Cite
|
Sign up to set email alerts
|

Stable solvers for real-time Complex Langevin

Abstract: This study explores the potential of modern implicit solvers for stochastic partial differential equations in the simulation of real-time complex Langevin dynamics. Not only do these methods offer asymptotic stability, rendering the issue of runaway solution moot, but they also allow us to simulate at comparatively large Langevin time steps, leading to lower computational cost. We compare different ways of regularizing the underlying path integral and estimate the errors introduced due to the finite Langevin t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…A study of implicit schemes to numerical evolve the complex Langevin equation is found in ref. [30]. The Lee-Yang theorem states that the magnetic equation of state in the symmetric phase exhibits branch cuts that end at the edge singularities.…”
Section: Methodsmentioning
confidence: 99%
“…A study of implicit schemes to numerical evolve the complex Langevin equation is found in ref. [30]. The Lee-Yang theorem states that the magnetic equation of state in the symmetric phase exhibits branch cuts that end at the edge singularities.…”
Section: Methodsmentioning
confidence: 99%
“…The long-term goal of this line of study is to realize genuine real-time simulations of quantum fields on the lattice (see e.g. our work on complex Langevin [18] ). However as an intermediate time goal I see the realization of gauge invariant simulations of the real-time dynamics of classical lattice gauge theory.…”
Section: Pos(lattice2022)385mentioning
confidence: 99%
“…In a previous publication [8] we have shown how to avoid runaway trajectories, by introducing inherently stable solvers to the solution of the complex Langevin dynamics. In contrast to the adaptive step size prescription [9] discussed in the literature, the implicit solvers also provide a novel mechanism to regularize the underlying path integral we wish to simulate.…”
Section: Introductionmentioning
confidence: 99%